Expression of alveolar macrophage adhesion molecules in pulmonary sarcoidosis - Stříž, Ilja; Wang, You-Ming; Kalaycioglu, Oya; Costabel, Ulrich (Chest, 1992)
Beta-2-integrins belong to a family of leukocyte surface glycoproteins that are essential for immune functions of bronchoalveolar cells. The expression of three alpha chains designed as CD11a, CD11b, CD11c, a common beta chain CD18, and of a ligand for several integrins CD54 (ICAM-1) was studied on alveolar macrophages of patients with active and inactive sarcoidosis and in control subjects. The percentage of macrophages expressing CD11b (CR3) was significantly increased in patients with active sarcoidosis compared with patients who had inactive disease and control subjects. The adhesion molecule CD54 (ICAM-1) was detected on a higher percentage of alveolar macrophages in patients with active rather than inactive sarcoidosis and in control subjects. Since integrin-mediated adhesion seems to be important in macrophage-lymphocyte interactions during the immune response, higher expression of both CD11b and CD54 on sarcoid alveolar macrophages may be related to several immune abnormalities reported in pulmonary sarcoidosis.
Keywords: sarkoidóza; dospělí; Macrophages, Alveolar; receptory leukocytové adheze; Integrins; bronchoalveolární lavážní tekutina; Humans; antigeny CD18; Receptors, Leukocyte-Adhesion; plicní nemoci; Cell Adhesion Molecules; Lung Diseases; CD antigeny; mezibuněčná adhezivní molekula-1; Bronchoalveolar Lavage Fluid; mužské pohlaví; CD11 Antigens; antigeny CD11; Antigens, CD; Adult; Sarcoidosis; integriny; ženské pohlaví; Female; alveolární makrofágy; Immunoenzyme Techniques; lidé; imunoenzymatické techniky; Male; Intercellular Adhesion Molecule-1; molekuly buněčné adheze; CD18 Antigens